Meningoencephalitis tuberculosis as a paradoxical response to anti-tuberculous therapy in a child with pulmonary tuberculosis - a case report - Heda Melinda Nataprawira (Indonesian Pediatric Society Publishing House, 2016)
This paper reports a case of meningoencephalitis tuberculosis as a paradoxical response to anti-tubercu- lous therapy in a child with pulmonary tuberculosis.